PENGARUH INVESTASI DAN BELANJA PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DAN PAD DI KABUPATEN BERAU - U, Abdurrahman (Faculty of Economics and Business, University of Muhammadiyah Malang, 2013)
The first purpose of the research was to determine the direct and indirect influence of Investment and Government Expenditure on Economic Growth and Regional Income in Berau, while the second purpose was to identify the direct influence of Economic Growth on Regional Income in Berau. In order to get accurate results, the research implemented 2 regression lines to analyze the data. The finding shown in Line Diagram 1 indicated that investment and government expenditure had a direct and significant effect on economic growth in Berau. Meanwhile, on the Line Diagram 2, it appears that investment and government expenditure had a direct effect and an indirect but significant impact on Regional Income in Berau.